Security affairs of islamic Jerusalem (Bayt al-Maqdis) after the first Muslim conquest 637CE : a historical and analytical study - Aminurraasyid Yatiban; Fatimatuzzahra Abd Rahman (2012)
For a long time Islamicjerusalem which is also known as Bayt al-Maqdis has seem to be a vulnerable region attracting attention from various parties. With the coming of the Muslims to liberate Islamicjerusalem in 637CE, the situation inside and outside the territory seems to have experienced various kinds approach. The Muslims employed their concept of sovereignty over the territory, which emphasised on the security issues. In this paper, the researcher endeavours to examine the issues of safety and relevant matters in relation to territorial security as significant elements in implementing the Muslim concept of sovereignty over Islamicjerusalem. Some of the questions needed to be addressed here: Did they successfully implement that concept? What kind of security measures were taken by Muslim sovereigns to secure Islamicjerusalem? What role did the non-Muslims play their roles in securing the region? The researcher attempts to employ multi-disciplinary research methodologies in conducting this research. While, historical research methodology is widely used to investigate significant historical facts and records, Islamic research methodology will also be employed to provide a basis of Muslim understandings towards an element of concept of sovereignty, namely, ‘security’.